2017
DOI: 10.1002/admi.201700462
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Photoinduced Wettability Switching on Nanoporous Titania Surfaces under Oil

Abstract: Figure 4. LuCY (Langmuir-Hinshelwood Cassie-Baxter Young) model relates photocatalysis directly to wetting using the well-known Langmuir-Hinshelwood and Cassie-Baxter models. k p , k c , and k -c are the photocatalysis, adsorption, and desorption rate constants, respectively. f s and f cs are the area fractions of clean and oil-contaminated sites on the TiO 2 surface. w,o * θ is the water-in-oil contact angle of a sessile drop on the TiO 2 nanostructured surface. www.advancedsciencenews.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Manipulating the membrane’s wettability has been reported as an alternative to enhance its fouling resistance 22 25 . For example, membranes with hydrophilic (i.e., water contact angle < 90°) or superhydrophilic (i.e., water contact angle 0°) wettability can prevent adsorption of the organic substances (e.g., oil) to the surface by allowing water to form a thin film 26 – 28 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Manipulating the membrane’s wettability has been reported as an alternative to enhance its fouling resistance 22 25 . For example, membranes with hydrophilic (i.e., water contact angle < 90°) or superhydrophilic (i.e., water contact angle 0°) wettability can prevent adsorption of the organic substances (e.g., oil) to the surface by allowing water to form a thin film 26 – 28 .…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the permeate flux upon light illumination has been attributed to the photocatalytic degradation of the organic substances deposited on the membrane surface 27 , 48 , 49 . Also, such photocatalytic membranes have demonstrated that they exhibit a time-dependent evolution of the surface chemistry heterogeneity (e.g., clean and contaminated regions) upon light illumination which can be quantitatively described by the contact angle measurements 6 , 22 , 50 52 . To our knowledge, quantitative relationships of the evolution of surface chemistry heterogeneity on a membrane surface and that of permeate flux upon visible light illumination are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photocatalytic materials generate electron hole (e − ‐h + ) pairs upon irradiation of light with an energy greater than their bandgap energy ( E g ). [ 33 ] The electrons and holes react with ambient oxygen or water molecules and produce highly reactive radicals such as hydroxyl, [ 34–36 ] superoxide anion, [ 37 ] and peroxide. [ 38 ] These radicals oxidize (or reduce) the organic contaminants either dissolved in the water‐rich permeate or on the membrane, which results in decontamination of the permeate and membrane cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of wettability on tribological property needs to be further studied [24, 25]. It is worth mentioning that surface wettability can be controlled by applying external stimuli, such as pH, light, electricity, and temperature, which provides a basis for investigating the influence of wettability on tribological performance [26–30].…”
Section: Introductionmentioning
confidence: 99%